Assessment of Heavy Metals in selected Medicinal Plants in Bayelsa State, Nigeria - Eneni R. Inala (Nigerian Journal of Pharmaceutical and Applied Science Research, 2025)
Background: The study evaluated the concentration of some toxic heavy metals in medicinal plants used widely in traditional medicine in Bayelsa State. The leaves of six medicinal plants (Stachytarpheta jamaicensis, Justicia secunda, Cleome viscosa, Ipomoea aquatica, Ipomoea cairica and Solenostemon monostachyus) growing their natural habitats were collected and analyzed for seven heavy metals. Methods: The concentrations of the heavy metals (Cadmium, Lead, Arsenic, Chromium, Zinc and Mercury) were determined using standard procedures and Varian Spectra A100 Atomic Absorption Spectrophotometer. Results: The results indicate the plants had differential accumulation of the heavy metals that were mostly within the permissible concentration thresholds set by the WHO. Lead significantly accumulated in all the plant species. Conclusion: The need for constant monitoring, and collection of medicinal plants from an unpolluted area or areas with minimal contamination is essential and highlighted.